Neonatal chronic myeloid leukaemia with prolonged survival. Issue 1 (January 1983) - Moir, D J; Emerson, P M; Holmes-Siedle, M; Moncrieff, M W; Ellis, H
Abstract : An 11-day-old girl presented with an atypical form of chronic myeloid leukaemia. The clinical course was unusually benign, but terminated in blast cell transformation at age 8½ years. Remission was obtained and followed by a successful bone marrow transplant.